Training on Clothing Design from Sarung Material as a Tourism Icon in Malang City - Redjeki, Endang Sri; Choiro, Umu Da'watul; Listyaningrum, R. Anggia; Haidar, Muslim (Universitas Negeri Padang, 2024)
The Polowijen cultural village, Malang City, is packaged educationally for visiting tourists, this is to introduce the culture of Malang City which is still preserved and managed by the residents of Polowijen Village. Sarong cloth is a cloth that is used every day and can be used as a potential for cultural development in Polowijen Village. The method used in this community service activity is the method. The implementation method is a way of carrying out activities by determining activity steps related to the problems faced by The community, in this case, are the tailors who are members of the KWP group, with a network of cooperation, participatory work action and monitoring. Based on the results of the service regarding branding sarongs as several clothing options, it can be concluded as follows: (1) Polowijen Village, Malang City, has now branded itself as a sarong sewing center with various types of clothing products. (2) The tailors in Polowijen are more creative and collaborate more with each other in making sarongs as creative as possible. (3) Collaboration was established between the tailors and the Polowijen sub-district cooperative and the Malang City Trade and Industry Department which was able to increase sarong sales figures. (4) There has been an increase in the economy as evidenced by the relatively cheap purchase price of sarong cloth which can achieve profits of up to 200% for every production of 1 sarong cloth.